The nature of sports coach development in China: What are we trying to achieve? - Li, S.; Carson, H. J.; Collins, D. (International Sport Coaching Journal, 2025)
Coach education and continuing career development have become a significant focus of global discussion within the sport domain. Current mainstream strategies for developing and assessing coaches in most countries, including China, are based on competency-based systems. However, there are many shortcomings of this system, especially when considering the varied practical challenges and needs of coaches and athletes; in short, such an approach does not facilitate enough adaptability. The purpose of this article is to critically review the literature, exploring both competence- and expertise-based coach development systems and their implications for coaching practice in China. First, we introduce and discuss the competency-based approach, including its strengths and weaknesses and how this applies within the Chinese development system. Next, we introduce and evaluate an alternative, expertise-based development system characterized by adaptability and greater inclusiveness within the coaching domain, which is underpinned by a distinct set of cognitive decision-making skills from the coach`s perspective. In addition, we expand this discussion by explaining the implications of this approach for coach assessment and offer some future suggestions for research in this area.